Microbial RNA, the New PAMP of Many Faces - Milillo, M. Ayelén; Velásquez, Lis N.; Barrionuevo, Paula (Frontiers in Tropical Diseases, 2022)
Traditionally, pathogen-associated molecular patterns (PAMPs) were described as structural molecular motifs shared by different classes of microorganisms. However, it was later discovered that the innate immune system is also capable of distinguishing metabolically active microbes through the detection of a special class of viability-associated PAMPs (vita-PAMPs). Indeed, recognition of vita-PAMPs triggers an extra warning sign not provoked by dead bacteria. Bacterial RNA is classified as a vita-PAMP since it stops being synthesized once the microbes are eliminated. Most of the studies in the literature have focused on the pro-inflammatory capacity of bacterial RNA on macrophages, neutrophils, endothelial cells, among others. However, we, and other authors, have shown that microbial RNA also has down-modulatory properties. More specifically, bacterial RNA can reduce the surface expression of MHC class I and MHC class II on monocytes/macrophages and help evade CD8+ and CD4+ T cell-mediated immune surveillance. This phenomenon has been described for several different bacteria and parasites, suggesting that microbial RNA plays a significant immunoregulatory role in the context of many infectious processes. Thus, beyond the pro-inflammatory capacity of microbial RNA, it seems to be a crucial component in the intricate collection of immune evasion strategies. This review focuses on the different facets of the immune modulating capacity of microbial RNA.